Context management for heterogeneous administrative domains - Meneses, Filipe (2004)
When accessing user context, context-aware applications often interact directly with sensors or have to deal with specific space representations. This work addresses context representation and management for mobile users. It proposes a generic solution based on a Context Container where the user context can be represented by an unlimited number of dimensions. The proposed solution is based on a Context Manager that integrates the raw data acquired by sensors and enriches user context with new calculated and estimated dimensions.